2012
DOI: 10.1002/ange.201205693
|View full text |Cite
|
Sign up to set email alerts
|

Filme molekularer Bewegungen und Reaktionen: Einzelmolekültransmissionselektronenmikroskopie in Echtzeit

Abstract: “The truth is, the Science of Nature has been already too long made only a work of the Brain and the Fancy: It is now high time that it should return to the plainness and soundness of Observations on material and obvious things,” das erklärte der stolze Robert Hooke in seinem Bildband von Mikroskop‐ und Teleskopbildern “Micrographia” im Jahre 1665. In der Chemie ist Hookes Äußerung heute noch gültig, wo ein erheblicher Arbeitsanteil notwendigerweise im Gehirn und durch Einbildungskraft stattfindet. Die Einzelm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…[22] An image of MINT pp -1 obtained under a JEOL-JEM 2100F microscope (2.5 resolution), like the microscope utilized by Nakamura and co-workers in their seminal study, [23] is shown in Figure 6 c. Most of the individual SWNTs show densely covered walls (Figure 6 c, white ellipse), in agreement with the high degree of functionalization determined by TGA, but we were pleased to observe that in numerous cases distinct circular objects could be detected around the nanotubes, in several different areas of the sample (Figure 6 c, white circles). Pioneering studies by Nakamura and co-workers have offered extensive evidence of the observation of a variety of small organic molecules under TEM in the vicinity of carbon nanotubes.…”
Section: Methodsmentioning
confidence: 99%
“…[22] An image of MINT pp -1 obtained under a JEOL-JEM 2100F microscope (2.5 resolution), like the microscope utilized by Nakamura and co-workers in their seminal study, [23] is shown in Figure 6 c. Most of the individual SWNTs show densely covered walls (Figure 6 c, white ellipse), in agreement with the high degree of functionalization determined by TGA, but we were pleased to observe that in numerous cases distinct circular objects could be detected around the nanotubes, in several different areas of the sample (Figure 6 c, white circles). Pioneering studies by Nakamura and co-workers have offered extensive evidence of the observation of a variety of small organic molecules under TEM in the vicinity of carbon nanotubes.…”
Section: Methodsmentioning
confidence: 99%
“…Pioneering studies by Nakamura and co-workers have offered extensive evidence of the observation of a variety of small organic molecules under TEM in the vicinity of carbon nanotubes. [22] An image of MINT pp -1 obtained under a JEOL-JEM 2100F microscope (2.5 resolution), like the microscope utilized by Nakamura and co-workers in their seminal study, [23] is shown in Figure 6 c. Most of the individual SWNTs show densely covered walls (Figure 6 c, white ellipse), in agreement with the high degree of functionalization determined by TGA, but we were pleased to observe that in numerous cases distinct circular objects could be detected around the nanotubes, in several different areas of the sample (Figure 6 c, white circles). The diameter of the nanotubes (ca.…”
Section: Methodsmentioning
confidence: 99%